A research on the stickiness of gradient process for regional economy based on grey clustering. (5th January 2015) - Min, Wei
From the current situation of regional economic development in China, we can see that the developed areas are still developed while backward areas are still lagging behind. Obviously, the traditional industry gradient theory cannot explain this situation. Because in a system of regional Gradient, especially in China where the system is full of labour-intensive industries, and there are many factors that slow down the process of regional Gradient which resulting in a regional gradient transfer of viscous. To describe and evaluate the stickiness of grade more accurately and based on the perspective of grey clustering, this paper used seven definitions and eight steps to analyse China's regional economic Gradient Stickiness Model and get some conclusion.